Gambaran Persepsi Mahasiswa Profesi terhadap Budaya Keselamatan Pasien - Nabila, Rossa; Juliawati, Mita (e-GiGi, 2025)
Abstract: Patient safety is a major thing of concern worldwide, particularly for medical personnel in preventing patient injuries during treatment. Patient safety incidents are also a concern for the government and the health community in Indonesia. This study aimed to obtain the perception of patient safety culture among professional students at the Faculty of Dentistry, Universitas Trisakti, specifically at RSGM-P FKG Usakti. This was a descriptive and observational stufy with a cross-sectional design conducted through online. The total number of respondents in this study was 250 professional students at RSGM-P Faculty of Dentistry, Universitas Trisakti. The results showed a response rate of 56.1%. Positive patient safety culture values were at 46.8%, while negative patient safety culture values were at 53.2%. Categorically, positive patient safety culture values were rated as very good (23.2%), good (23.6%), moderate (30.8%), and poor (22.4%). Meanwhile, negative patient safety culture values were rated as moderate (30.8%) and poor (22.4%). In conclusion, patient safety factors still dominate positive perceptions of professional students. Despite the slightly higher percentage of negative patient safety culture value compared to positive value. safety climate factor still dominates the perception of professional students. Keywords: perception; professional dentistry students; patient safety culture    Abstrak: Keselamatan pasien merupakan hal utama yang menjadi perhatian masyarakat dunia khususnya tenaga medis guna mencegah terjadinya cedera pasien selama perawatan. Insiden keselamatan pasien juga menjadi perhatian bagi pemerintah maupun masyarakat kesehatan di Indonesia. Penelitian ini bertujuan untuk mengetahui gambaran dan persepsi budaya keselamatan pasien (BKP) pada mahasiswa profesi di RSGM-P FKG Universitas Trisakti. Jenis penelitian ialah observasional deskriptif dengan desain potong lintang yang dilakukan secara daring. Jumlah responden penelitian ini sebanyak 250 mahasiswa profesi di RSGM-P FKG Usakti. Hasil penelitian mendapatkan response rate sebesar 56,1%. Nilai BKP positif sebesar 46,8%, nilai BKP negatif sebesar 53,2%. Kategori nilai BKP positif ialah nilai sangat baik (23,2%), baik (23,6%), sedang (30,8%), dan kurang (22,4%).Simpulan penelitian ini ialah faktor budaya keselamatan pasien masih mendominasi persepsi positif para mahasiswa profesi. Walaupun hasil nilai budaya keselamatan pasien menunjukan negatif sedikit lebih tinggi daripada positif tetapi faktor keselamatan atau safety climate masih mendominasi persepsi para mahasiswa profesi. Kata kunci: persepsi; mahasiswa profesi Kedokteran Gigi; budaya keselamatan pasien